Audit Configuration and Vulnerability Router on Diskominfos of Bali Province - gede ardi herdiana (International Journal of Engineering and Emerging Technology, 2021)
Abstract-Network security system on a computer that connected to the internet must be well planned and understood in order to effectively protect the resource in the network. how to find out the vulnerability of a network, so that by knowing the weaknesses in the network, then steps to overcome this drawback can be done. One of the forms taken includes conducting periodic analysis, both logical and physical. so that later it is expected that the analysis will produce an audit report containing the detection of various existing vulnerabilities, then take appropriate protective steps, which needed as a guarantee of security for the sustainability of the system. Nipper works by benchmarking the configuration of a router. After completing the inspection, you can see the configuration information as well as the security level of the router. Nessus works by scanning predetermined targets, such as a set of hosts or a separate host. Once the scan activity is complete, you can see the result information in either a graph or a line